Hak Asasi Manusia Beragama Dalam Perspektif Tafsir Izwaji (Human Rights In The Perspective Of Izwaji's Tafsir) - Musthofa Musthofa (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2019)
Religious human rights, is the right of a person to embrace a religion that is believed to be true. Basically, religious human rights are one's freedom to embrace a religion that is believed to be true. Human Rights in the Perspective of Izwaji's Tafsir includes: First, the right of faith, including pledges by word of mouth, justification with the heart and justification through the deeds of the limbs. Second, the right to practice includes the principle of compliance, the principle of fulfillment, the right of principle and justice. Third, the right to protection, including physical and legal protection, includes the expression of thought, preaching, which includes freedom, rational and universal preaching, and protection of maisyah (economic resources) among fellow believers.